The Role of Surgery to Relieve Symptomatic Cutaneous T-Cell Lymphoma Refractory to Medical Treatments - Wesley Q. Zhang; Emily E. Hecox; Shireen Dogar; Marc E. Walker (Case Reports in Oncological Medicine)
Conclusion: Surgical intervention, in addition to established medical standards of care, for symptomatic relief of compression neuropathy from tumor mass effect for refractory CTCL should be considered to achieve quality of life goals for patients.